A powerful convergence: Community schools and early childhood education. (February 2018) - Jacobson, David
Communities around the country are converging on a new approach to raising achievement for low-income children. This approach draws on two reform movements: (1) full-service community schools that provide wraparound health and social services to children and families, and (2) Prenatal through Grade 3 initiatives to improve quality, alignment, and coordination across early childhood and early elementary education. Examples in Cincinnati, Omaha, and Multnomah County demonstrate how communities can develop effective, results-oriented partnerships among elementary schools, community-based preschools, and other early childhood organizations .